Discrete Survival Model Analysis of Plasmodium falciparum Response to Artemisinin-Based Combination Therapies among Children in Regions of Varying Malaria Transmission in Cameroon - Akindeh M. Nji; Innocent M. Ali; Peter Thelma Ngwa Niba; Evehe Marie-Solange; Christian Heumann; Guenter Froeschl; Wilfred F. Mbacham (Pathogens, 2021)
The need to monitor changes in parasite clearance following treatment with artemisinin-based combination therapies (ACTs) is important in the containment of drug resistance. This study aimed to model Plasmodium falciparum response to ACTs among children in two different transmission settings (Mutengene and Garoua) in Cameroon. Using the step function, a discrete-time survival model was fitted with all the covariates included that might play a role in parasite clearance. The probability of clearing parasites within 24 h following treatment was 21.6% and 70.3% for younger children aged 6 to 59 months and 29.3% and 59.8% for older children aged 60 to 120 months in Mutengene and Garoua, respectively. After two days of treatment, the conditional probability of clearing parasites given that they were not cleared on day 1 was 76.7% and 96.6% for children aged 6–59 months and 83.1% and 93.5% for children aged 60–120 months in Mutengene and Garoua, respectively. The model demonstrated that the ecological setting, age group and pretreatment serum levels of creatinine and alanine aminotransferase were the main factors that significantly influenced parasite clearance in vivo after administration of ACTs (p < 0.05). The findings highlight the need for further investigations on host differential response to ACTs in current practice.